Effects of Hearing Loss and Cognitive Load on Speech Recognition with Competing Talkers - Meister, Hartmut; Schreitmüller, Stefan; Ortmann, Magdalene; Rählmann, Sebastian; Walger, Martin (Frontiers in Psychology, 2016)
Everyday communication frequently comprises situations with more than one talker speaking at a time. These situations are challenging since they pose high attentional and memory demands placing cognitive load on the listener. Hearing impairment additionally exacerbates communication problems under these circumstances. We examined the effects of hearing loss and attention tasks on speech recognition with competing talkers in older adults with and without hearing impairment. We hypothesized that hearing loss would affect word identification, talker separation and word recall and that the difficulties experienced by the hearing impaired listeners would be especially pronounced in a task with high attentional and memory demands. Two listener groups closely matched for their age and neuropsychological profile but differing in hearing acuity were examined regarding their speech recognition with competing talkers in two different tasks. One task required repeating back words from one target talker (1TT) while ignoring the competing talker whereas the other required repeating back words from both talkers (2TT). The competing talkers differed with respect to their voice characteristics. Moreover, sentences either with low or high context were used in order to consider linguistic properties. Compared to their normal hearing peers, listeners with hearing loss revealed limited speech recognition in both tasks. Their difficulties were especially pronounced in the more demanding 2TT task. In order to shed light on the underlying mechanisms, different error sources, namely having misunderstood, confused, or omitted words were investigated. Misunderstanding and omitting words were more frequently observed in the hearing impaired than in the normal hearing listeners. In line with common speech perception models, it is suggested that these effects are related to impaired object formation and taxed working memory capacity (WMC). In a post-hoc analysis, the listeners were further separated with respect to their WMC. It appeared that higher capacity could be used in the sense of a compensatory mechanism with respect to the adverse effects of hearing loss, especially with low context speech.